2012
DOI: 10.1167/12.8.7
|View full text |Cite
|
Sign up to set email alerts
|

The motion-induced shift in the perceived location of a grating also shifts its aftereffect

Abstract: Motion can bias the perceived location of a stationary stimulus, but whether this occurs at a high level of representation or at early, retinotopic stages of visual processing remains an open question. As coding of orientation emerges early in visual processing, we tested whether motion could influence the spatial location at which orientation adaptation is seen. Specifically, we examined whether the tilt aftereffect (TAE) depends on the perceived or the retinal location of the adapting stimulus, or both. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
(41 reference statements)
0
17
1
Order By: Relevance
“…Although negative face aftereffects can emerge following brief adaptation [31, 32], like they sometimes do for basic features [33, 34], serial dependence on the timescale of our experiments trumped any potential negative aftereffects.…”
Section: Discussionmentioning
confidence: 80%
“…Although negative face aftereffects can emerge following brief adaptation [31, 32], like they sometimes do for basic features [33, 34], serial dependence on the timescale of our experiments trumped any potential negative aftereffects.…”
Section: Discussionmentioning
confidence: 80%
“…Having a flash to mark the intended alignment point removes these constraints, and as we show here, entails no loss of the size of the effect. It allows us to present the flash when the point of interest approaches vertical, even if there are several otherwise identical points (a multiple cycle grating), or if the texture is random, as we have previously shown (Tse et al, 2011; Kosovicheva et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…The recent demonstration that motion can have widespread influence on activity in retinotopic cortex (Harvey and Dumoulin, 2016) also provides some plausibility to our findings, even if the two sets of findings may not be driven by the same mechanism. Recent psychophysical evidence has demonstrated that shifting the perceived position of a grating using the flash grab effect leads to a corresponding shift in the location of the tilt aftereffect elicited by the grating (Kosovicheva et al, 2012), corresponding to about 10% of the perceived shift. Neurophysiological studies have indicated that the tilt aftereffect is driven by adaptation of orientation-selective cells in V1 (Movshon and Lennie, 1979), so this result suggests that at least some aspect of the mechanism underlying motion-induced position shifts can be attributed to early visual cortex.…”
Section: Discussionmentioning
confidence: 99%